Online Marketing Through Consumers: A Study Of Effectiveness Of Various Tools And Techniques Across Industries - RIZ ‘V, LUBNA (British Journal of Marketing Studies, 2013)
This research is conducted to see how the consumers’ brand perception and purchasing decisions are influenced by different online marketing tools used across the industries such as Word of Mouth (WOM), online Chat assistance and Email advertising. Its purpose was so study the relationship between the different online marketing tools and techniques, WOM, Online chat and Email and their effects on the brand perception and consumer purchasing decision. There are a lot of other influencing factors included in a decision making of a consumer for purchasing and developing a perception about a particular brand but the most important factors that play a defining role in changing the consumer brand perception and purchasing decision is WOM and the dependency exists on these three variables. Our results show that the residents of Karachi who are active on internet prefer WOM over the other two variables which are online chat and email advertising. Different companies avail the online marketing strategy of WOM service in order to attract the potential customers and influence their purchasing decision and brand perception. There are no generalized factors that affect the consumer decision of purchasing and developing a brand perception in Karachi. WOM is being done by the consumers and it’s one of the cheapest medium of online marketing which is being availed by many companies and proved to be effective.